Integrating English for Specific Academic Purposes (ESAP) skills into mainstream English courses - Sánchez Hernández, Purificación; Pérez Paredes, Pascual Francisco (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2002)
This paper examines the design and implementation stages of a course of English given at the Faculty of Psychology of the University of Murcia, Spain. The course was programmed regardless of the particular individuals and no previous requirements were needed. Two initial tests were passed to the students at the beginning of the semester: the first one to evaluate their needs and motivation and the second one to measure their general communicative competence. The results were heterogeneous. The students were informed of their results and also of the level they should reach to pass the course, especially those with low marks. With respect to their motivation they manifested two orientations: Labour and integrative reasons. Taking into account their 'labour reasons' some units closely related to their speciality were included and the final evaluation was modified giving some weight also to the specific English component (75 % GE, 25 % ESAP). The analysis reveals that, according to our initial assumption, those students with a better communicative competence at the beginning of the course obtained the best results in the final exam. A correlation between those students with intrinsic motivation and communicative competence and the best final marks has also been found.